Chemical transformation of a long-chain alkyl organosulfate via heterogeneous OH oxidation: a case study of sodium dodecyl sulfate. Issue 5 (20th June 2022) - Madeleine Ng, Sze In; Ng, Kwan Hung; Felix Yeung, Pui Wo; Xu, Rongshuang; So, Pui-Kin; Huang, Yuanlong; Yu, Jian Zhen; Choi, Chun Kit K.; Steve Tse, Ying-Lung; Chan, Man Nin
Abstract : Sodium dodecyl sulfate undergoes heterogeneous oxidation by hydroxyl radicals, and its reactivity is enhanced when ammonium ions are present in aerosols. Abstract : Organosulfates (OSs) are regarded as stable tracers of secondary organic aerosols. However, recent studies have reported their potential chemical instability, which is dependent on their structures. In this study, we aim to investigate the transformation and kinetics of a long-chain alkyl OS upon heterogeneous hydroxyl radical (OH) oxidation. We selected sodium dodecyl sulfate (SDS, C12 H25 O4 SNa) as a model compound due to its atmospheric relevance. We conducted experiments using an oxidation flow reactor at 80% RH and room temperature. We analyzed the reaction kinetics and products by liquid chromatography-mass spectrometry and ultrahigh-resolution mass spectrometry. We quantified inorganic sulfate formation by ion chromatography. We have proposed reaction pathways based on aerosol composition data. Our results reveal that dodecyl sulfate decays at (4.09 ± 0.09) × 10 −13 cm 3 per molecule per s with an atmospheric lifetime of ∼19 days upon heterogeneous OH oxidation. Compared with the literature results, we observe a significant kinetics enhancement when ammonium sulfate is present in aerosols. Our molecular dynamics simulations suggest that ammonium ions tend to displace sodium ions from the air–water interface and attract OH more strongly, which promotes collisions between dodecyl OS and OH. Therefore, the effects of counterions on surface-active organics should be considered during interpretation of experimental kinetics data. We detected sequential oxygenation of dodecyl sulfate, which dominated over fragmentation and inorganic sulfate formation. Our identified products indicate a potential source of some oxygenated aliphatic C6 - to C10 - and C12 -OS detected in the atmosphere. Collectively, our work highlights the need for more comprehensive investigations of structural factors governing OS chemistry.